The Cartesian mastery of Nature: Descartes and the disenchantment of the world - García Rodríguez, Sergio (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
This paper analyzes the strategies performed by Descartes in order to «disenchant the world» for removing the hermetic elements from the Cartesian scientific explanations and subjecting all the natural phenomena to our control. To do this, I appeal to the distinction between causal elements —occult qualities— and their effects —admirable virtues— as the two dimensions that must be incorporated under the scientific explanations to ensure the calculation of phenomena and their mastery.